Study protocol for OtoSurg 1: A prospective evaluation of worldwide tonsillectomy indications, techniques, and outcomes - Zachary Elwell; Emma Finnegan; Kartik Motwani; Juyun Hwang; Caretia Washington; Katharine G. Johnson; Audrey Y. Su; Rolvix H. Patterson; Zhen Jason Qian; Catherine A. Shaw; Taseer Din; Maxwell P. Kligerman (PLoS ONE, 2026)
Background Tonsillectomy is the most common pediatric surgery performed globally, yet little is known about how tonsillectomy outcomes vary worldwide. Preliminary Data Although generally considered a safe surgery, tonsillectomy carries significant risks. Approximately 3% of US children require hospital readmission within 30 days due to life-threatening complications. While mortality rates in high-income countries (HICs) are relatively low (~0.0005%), mortality rates in low- and middle-income countries (LMICs) are not well characterized, with some reports suggesting rates many times higher (~3%). Research gap Despite the frequency and significance of tonsillectomy, it remains unclear how surgical indications, techniques, and settings may impact outcomes worldwide. In addition, there is currently no mechanism to perform a prospective investigation of global tonsillectomy outcomes. Hypotheses and specific aims We hypothesize that the morbidity and mortality of routine tonsil surgery vary significantly according to geographic region and healthcare setting, as well as surgical indications and techniques. We aim 1) to quantify global variation in 30-day major postoperative complications and mortality following pediatric tonsillectomy across World Health Organization (WHO) regions and 2) to characterize global variation in pediatric tonsillectomy surgical indications and operative techniques across WHO regions. Design OtoSurg 1 will be an international, multi-site, prospective cohort study. The central IRB is approved and hosted by Emory University (IRB ID: STUDY00009113). All healthcare facilities globally that perform pediatric tonsillectomy will be invited to participate. Participating investigators will be trained to collect data on patients undergoing primary tonsillectomy over a 90-day period at their respective institutions. Site-based teams will record demographic data, surgical indication(s), surgical technique(s), postoperative complications, and mortality directly into a global de-identified tonsillectomy outcomes data registry. We will leverage existing relationships and professional networks to recruit participants from 30 sites in each of the six WHO regions for a target of 180 partner sites. Potential impact This study will highlight potential opportunities for intervention to standardize and improve outcomes for the world’s most common pediatric surgery, focusing on LMICs. Beyond its primary objectives, this project will also seek 1) to recruit and train a collaborative research network of otolaryngology surgeons from around the world and 2) to build the digital infrastructure necessary to support this network sustainably. This collaborative research network will serve as the foundation for future large-scale research initiatives and for the development and implementation of novel, data-driven interventions.